Blockchain Technology for Sustainable Management of Electricity and Water Consumption - Muath Alrammal; Fadi Abu-Amara; Zamhar Ismail; Muhammad Nadeem (Engineering Proceedings)
Electricity and water are vital resources, but the current management systems face challenges due to growing demand and regulatory complexities. To address this, we introduce a novel blockchain-based solution for managing electricity and water services. Our proposed system connects various entities through smart contracts on the blockchain, automates processes, and ensures transparency. Customers can easily view and pay bills, track consumption, and enjoy secure online transactions while preserving their privacy. The shared digital ledger enhances trust among entities and promotes transparency. Additionally, our system contributes to environmental sustainability by reducing paper usage, incentivizing energy-saving devices, and efficiently managing electricity and water consumption. Finally, a meta-analysis of the related work is conducted to highlight the importance of our solution.